Analysis of the Fusion of Postmodern Technology and Oil Painting Art in the Film "Loving Vincent" - Song, Shu (Transactions on Social Science, Education and Humanities Research, 2023)
This paper explores the unique fusion of postmodern technology and oil painting art in the film "Loving Vincent" and analyzes how this fusion impacts the aesthetics of the film. Firstly, the article introduces the application of oil painting art in cinema, as well as the utilization of rotoscoping techniques by the film’s production team to faithfully recreate Vincent van Gogh’s distinctive painting style within the movie, and how it captivates the audience, leaving a profound impression. Secondly, the paper delves into how postmodern technology enhances the visual effects of the film, allowing filmmakers to imbue the screen with the texture and texture of an oil painting, and how the elements and techniques of oil painting are seamlessly integrated into the film to offer a unique cinematic experience for the audience. Subsequently, the article analyzes the influence of this fusion on film aesthetics, including the embellishment of visual effects in film, the innovative interpretation of cinematic ambiance, and the expansion of narrative aesthetics in cinema. Finally, the paper concludes that the fusion of postmodern technology and oil painting art has introduced fresh creativity and aesthetic value to the realm of cinema, affording filmmakers greater artistic freedom while expanding the visual and aesthetic experiences of filmgoers, thus opening up new possibilities for the future of film production.